Prototype using arduino platform to analyze solar energy efficiency (International Journal of Geoscience, Engineering and Technology, 2023)
Our project consists of making the most of solar energy during the day using photovoltaic panels. A physical system and a logical system integrated with Arduino were developed where, through a sensor (luminosity, solar intensity or heat) it verifies the location of the sun and what is its maximum luminous intensity in the place, from which a solar panel follows the movement of the sun. sun in order to achieve the greatest solar capture. At sunset, the plate will return to its initial position, and on cloudy days when possible light breaks through the clouds through the system, it will be possible to assess the best production direction. Data were collected for 12 hours of variable solar incidence on the prototype and on a panel installed as conventional, that is, fixed, the wind rose was analyzed in view of the structure of the system, a comparison of results and a future projection of expansion of the system were carried out.